MODELLED MECHANISMS IN THE SLAKE-DURABILITY TEST FOR SOFT ROCKS - Didi S. Agustawijaya (Civil Engineering Dimension, 2003)
The slake-durability test is regarded as a simple test for assessing weathering of rocks. This simple test has been accepted as a standard test by the Rock Mechanics Society. However, mechanisms into slaking processes have not been fully understood yet as many factors involved in the processes. The current research explored mechanisms performed by the test by conducting a series of slakedurability tests for four types of soft rocks taken from Coober Pedy, South Australia. Results show that the slake-durability index (Id2) of weathered soft rocks was influenced by the degree of weathering. Distinctly weathered rocks had lower indeces compared to partly weathered rocks. Shapes also influenced the Id2 of these soft rocks. Different shapes displayed different mechanisms in the slaking processes. Samples that had irregular shapes tended to have a lower Id2 compared to samples that had rounded shapes. Thus, the slake-durability test might have simple procedures, but it could have complicated mechanisms in slaking processes that contribute to the result of the test.